Enhanced mitochondrial function in B cells from elderly type-2 diabetes mellitus patients supports intrinsic inflammation - Frasca, Daniela; Bueno, Valquiria (Frontiers in Aging, 2024)
In this paper, we measured B cell function in elderly healthy individuals (EH) and in elderly patients with Type-2 Diabetes Mellitus (T2DM, ET2DM), which are treatment-naive, as compared to healthy young (YH) individuals. Results show a higher serum inflammatory status of elderly versus young individuals, and especially of ET2DM versus EH. This status is associated with a reduced response to the seasonal influenza vaccine and with increased frequencies of the circulating pro-inflammatory B cell subset called Double Negative (DN) B cells. B cells from ET2DM patients are not only more inflammatory but also hyper-metabolic as compared to those from EH controls. The results herein are to our knowledge the first to show that T2DM superimposed on aging further increases systemic and B cell intrinsic inflammation, as well as dysfunctional humoral immunity. Our findings confirm and extend our previously published findings showing that inflammatory B cells are metabolically supported.